Testing the factor structure of the Forgiveness Scale among Italian adolescent students. Issue 6 (3rd July 2019) - Cabras, Cristina; Loi, Giorgia; Sechi, Cristina
ABSTRACT: The aim of the present study was to analysis the factor structure of the Italian version of the Forgiveness Scale (FS) among 663 adolescent students in Italy. The FS involves of 15 items measuring forgiveness toward the wrongdoer. This scale comprises two subscales, Absence of Negative (AN) and Presence of Positive (PP). These subscales evaluate the absence of negative and the existence of positive emotions, thoughts, and behavioural inclinations. Results suggests that only 11 of the original items are valid in the Italian version of the FS. In contrast to the original study, the two dimensions of forgiveness (AN and PP) were independent of each other in the current analysis. Evidence for convergent validity was also found. The results provide some initial support for the bi-dimensionality and internal consistency of the Italian FS and offer a starting point for future research to be pursued in forgiveness.